2018
DOI: 10.1007/s11030-018-9863-y
|View full text |Cite
|
Sign up to set email alerts
|

Facile and highly diastereo and regioselective synthesis of novel octahydroacridine-isoxazole and octahydroacridine-1,2,3-triazole molecular hybrids from citronella essential oil

Abstract: A novel and highly efficient synthetic approach for the expedite construction of new octahydroacridine-isoxazole- and octahydroacridine-1,2,3-triazole-based molecular hybrids is first reported. Rapid access to the octahydroacridine core was achieved in a highly diastereoselective fashion via cationic Povarov reaction of N-propargyl anilines and citronella essential oil (Cymbopogon nardus). The subsequent 1,3-dipolar and Cu (I) catalyzed alkyne-azide cycloaddition reaction of the terminal alkyne fragment with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This rational and relevant synthetic strategy prompts advantages such as broadening the pharmacological spectrum of several heterocycles and the enhancement in the therapeutic potential for specific ISSN 2056-9890 diseases (Mü ller-Schiffmann et al, 2012;Gü iza et al, 2019). Thus, some examples including OHA-isoxazole and OHA-1,2,3-triazole molecular hybrids have already been described (Acelas et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 99%
“…This rational and relevant synthetic strategy prompts advantages such as broadening the pharmacological spectrum of several heterocycles and the enhancement in the therapeutic potential for specific ISSN 2056-9890 diseases (Mü ller-Schiffmann et al, 2012;Gü iza et al, 2019). Thus, some examples including OHA-isoxazole and OHA-1,2,3-triazole molecular hybrids have already been described (Acelas et al, 2019).…”
Section: Chemical Contextmentioning
confidence: 99%
“…All geometrical calculations were done using the program Platon 25 . Table 1 summarizes the crystal data, intensity data collection and refinement details for (3). CIF file containing complete information on the studied structure was deposited with CCDC, deposition number 1954958, and is freely available upon request from the following web site:…”
Section: X-ray Data Collection and Structure Determinationmentioning
confidence: 99%
“…The 1,3-dipolar cycloaddition reaction is one of the most useful reactions for the synthesis of heterocyclic compounds [1][2][3][4] . It provides one of his best tools for constructing five-membered rings.…”
Section: Introductionmentioning
confidence: 99%
“…Authors [42] found that the use of the N-benzylanilines 21 and citronella EO, containing 45.7 % of citronellal allowed completing a highly diastereoselective process, which offers the easily separable trans-fused N-benzyl substituted OHAs 22 in good yields (Scheme 6). Although chiral chromatographic analysis is not yet available for this EO from native Colombian Cymbopogon nardus (content of citronellal enantiomer is unknown in the mixture), the citronella essential oil from C. nardus proved to be a cost-effective renewable source of citronellal to successfully create diverse functionalized OHA products as potential bioassays substrates [43].…”
Section: Citronella Oilmentioning
confidence: 99%